2019
DOI: 10.1051/0004-6361/201936019
|View full text |Cite
|
Sign up to set email alerts
|

The EREBOS project: Investigating the effect of substellar and low-mass stellar companions on late stellar evolution

Abstract: Eclipsing post-common envelope binaries are highly important for resolving the poorly understood, very short-lived common envelope phase of stellar evolution. Most hot subdwarfs (sdO/Bs) are the bare helium-burning cores of red giants which have lost almost all of their hydrogen envelopes. This mass loss is often triggered by common envelope interactions with close stellar or even sub-stellar companions. Cool companions to hot subdwarf stars such as late-type stars and brown dwarfs are detectable from characte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 43 publications
4
60
0
2
Order By: Relevance
“…Our simulations show successful envelope ejection for systems with BD companions as indicated by the observations. Also, the lower mass limit determined here is supported by observations: Despite considerable effort no giant planet has so far been identified in close orbit around a hot subdwarf yet (Schaffenroth et al 2019;Casewell et al 2018). However, there may be a bias because the lowest-mass companions are expected at longer periods of about 0.3 d. Otherwise, the companion would exceed its Roche lobe leading to mass transfer onto the primary (see Fig.…”
Section: Comparison To Observations Of Sdb Starssupporting
confidence: 82%
See 1 more Smart Citation
“…Our simulations show successful envelope ejection for systems with BD companions as indicated by the observations. Also, the lower mass limit determined here is supported by observations: Despite considerable effort no giant planet has so far been identified in close orbit around a hot subdwarf yet (Schaffenroth et al 2019;Casewell et al 2018). However, there may be a bias because the lowest-mass companions are expected at longer periods of about 0.3 d. Otherwise, the companion would exceed its Roche lobe leading to mass transfer onto the primary (see Fig.…”
Section: Comparison To Observations Of Sdb Starssupporting
confidence: 82%
“…However, there may be a bias because the lowest-mass companions are expected at longer periods of about 0.3 d. Otherwise, the companion would exceed its Roche lobe leading to mass transfer onto the primary (see Fig. 14 of Schaffenroth et al 2019). Such long-period systems are harder to follow up and only few of them have been investigated until now.…”
Section: Comparison To Observations Of Sdb Starsmentioning
confidence: 99%
“…Several sdB + brown dwarf systems are known, although typically seen with shorter orbital periods (e.g. Geier et al 2011;Schaffenroth et al 2015Schaffenroth et al , 2018Schaffenroth et al , 2019.…”
Section: Formation Historymentioning
confidence: 99%
“…Several ground-based surveys with both photometric and RV techniques target the red dwarf or brown dwarf close companions to hot subdwarfs (Schaffenroth et al 2018(Schaffenroth et al , 2019. These companions are frequent (Schaffenroth et al 2018), but no Jupiter-like planets have been found to date.…”
Section: Search For Planets Around Hot Subdwarfs: Current Statusmentioning
confidence: 99%
“…all known sdB+red dwarf or brown dwarf post-CE binaries have orbital periods below 1 d (Schaffenroth et al 2018(Schaffenroth et al , 2019(Schaffenroth et al , 2021.…”
Section: Cheops Performances For Hot Subdwarfsmentioning
confidence: 99%